COMPARATIVE STUDY OF THE USE OF ELECTRONIC AND CONVENTIONAL DICTIONARIES IN LEARNING VOCABULARY - Aulia Rizqa Handayani; Haryanto Atmowardoyo; Ahmad Talib (Universitas Negeri Makassar, 2022)
Vocabulary data plays an important role in mastering a language. This research is experimental research. The research sample was 60 students. The information collection instrument used was a questionnaire. The information analysis technique used statistical knowledge analysis Paired Sample T-Test. The results of this study indicate that there are differences in students' vocabulary data between students who are taught using the Electronic Dictionary (ED) and those who are taught using the Printed Dictionary (PD).